Hubungan Antara Keterampilan Metakognitif Dengan Kemampuan Kognitif dalam Desian dan Perencanaan Pembelajaran Pendidikan Agama Islam - Abdul Haris (Jurnal LENTERA: Jurnal Studi Pendidikan, 2020)
In facing the world of work, graduates need to have learning outcomes that allow them to take a set of smart and responsible actions in carrying out tasks in their field of work. To have smart and responsible actions they need to be trained and guided, so that they are accustomed to using their intelligence in dealing with learning difficulties. This intelligence is the embryo that enables the optimal operation of cognitive abilities as an effort to fully master learning outcomes. The carrying capacity for the functioning of these cognitive abilities requires metacognitive skills, namely strategic skills, how to manage and use thinking activities in certain learning methods. With the available support capacity, information, facts, or problems faced can be processed, recognized, understood by means of critical analytical thinking to further enrich one's knowledge (cognitive aspects). Data collection has been carried out to obtain information about the relationship of mastery of metacognitive skills with the level of cognitive abilities of Islamic Education students of STAI Al-Amin Dompu in designing instructional techniques for PAI learning. Based on the results of data analysis using the Moment Product Correlation statistical technique through statistical analysis using SPSS for Windows, a strong relationship was obtained between the metacognitive skills of students and their cognitive abilities in designing PAI learning instructional techniques. This is indicated by the value of the correlation coefficient or r count greater than r table (0.615> 0.361) at the 5% significance level. With a correlation coefficient of 0.615 (positive), indicating a strong correlation between metacognitive skills and students' cognitive abilities. Therefore, it can be concluded that the higher the metacognitive skills students have, the more they will affect their cognitive abilities. Based on the results of data analysis, it can be explained that cognitive abilities in terms of designing instructional techniques for teaching Islamic education will increase if students have the intelligence to use their metacognitive skills